Avaliação da formação acadêmica na perspectiva dos egressos de fisioterapia - Sampaio, Danielle Dorand Amorim (2020)
This research aimed to understand how graduates of Physiotherapy at the Federal University of Paraiba (UFPB) evaluate an academic training received in the course. Since its activation in Physiotherapy it has undergone several changes, one of which occurred after the implementation of the National Curricular Guidelines (DCN), determining changes in its training model. These changes contribute to the strengthening of the higher education evaluation process in Brazil. In 2004, it was regulated by the National Higher Education Assessment System (SINAES) and one of its innovations concerns the monitoring of students, which should be an integral part of educational practices, since it allows an assessment of institutional policies aimed at improving quality of courses. It can be used as a form of subsidiary changes in professional training and readjustments of the Pedagogical Course Project (PPC), according to the needs of the job market. For the theoretical basis of the research, the formation and institutionalization of Physiotherapy in Brazil and Paraiba was discussed, as well as the formation in the Physiotherapy course at UFPB, based on the studies by Vieira (2007) and Almeida (2012). In addition to addressing higher education and its assessment processes, emphasizing or accompanying treatment procedures such as research in the chambers (2006), Shiwa (2015) and Figueiredo (2015). In methodological terms, this research shows a quantitative and qualitative approach, of an applied nature, from a case study. Data collection was performed using an online questionnaire on Google Forms. For data analysis, statistical resources were used through the SPSS Program version 20.0 for Windows and the categorization technique present in the content analysis. It was concluded that the graduates make a good evaluation of the academic formation of the course, responding to the Physical Therapy DCN and to the PPC regarding the pedagogical model used. Highlighting the qualification of teachers, supervised internships, the ability to exercise the profession in an articulated manner to the social context, practical experience and participation in projects throughout the course. However, it is necessary to observe some points that seem to hinder professional training and performance, such as the physical and material structure, the teaching methodology on the part of some teachers, the updating of curricular content according to the changes that have occurred in society and improvement in business management. At the end of the research, guidelines were proposed for the integration and continuous evaluation of UFPB Physiotherapy graduates based on an evaluation culture, the development of a longitudinal research and the establishment of an effective bond of the graduate.